A ANALISIS TARJAMAH USLUB ISTIFHAM DALAM HADIS MUSLIM NO. 2581: RELEVANSINYA TERHADAP NILAI-NILAI ILMU SOSIAL ISLAM - Anwar, Hanifah; Rizky Amalia Putri; Intan Hafizatuz Zahrah; Nayla Audriva Cahyo; Huriyah Nabilah; M. Ahsanul Khuluq F.; Edidarmo, Toto (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2025)
This study examines the interrogation and application of hadiths from Imam Muslim no. 2581, as well as their significance for Islamic social knowledge. This study uses the Arabic linguistic method and content analysis to determine the structure and function of hadis. Per temuan penelitian, hadits in this form have a greater function and meaning than those in previous versions; they also cover rhetorical, pedagogical, and moral education components. While maintaining the integrity of the hadits, the analysis highlights many difficulties in translating the Islamic makna from Arabic to Indonesian. This study also identifies strong connections between the interogatif gaya found in hadiths and contemporary Islamic principles, such as social justice, human rights, and the development of strong communities. These tenets aid in the development of strategies for understanding hadits in the context of the modern world and advancing hadit analysis from an Arab linguistic perspective.